Sewanee in stone - Bowman, David (Sewanee, Tenn. : Proctor's Hall Press, 2003)
This is a history of the stone architecture on the campus of the University of the South, Sewanee, Tennessee. Included is information about the methods of construction and uses of the buildings, as well as stories about the architects and builders and university officers who were involved.
Includes bibliographical references and index
ARC
Department of Architecture
Keywords: Architecture; Stone buildings -- United States